Исследование комплексообразования ионов Mn(II) с пи- ридоксином в водной среде - Պատ․ խմբ․՝ Ա․ Լ․ Մնջոյան (1957-1962); Գլխ․ խմբ․՝ Գ․ Տ․ Թադևոսյան (1962-1973); Մ․ Հ․ Ինճիկյան (1974-1976) (ՀՍՍՀ ԳԱ հրատ․)
Методами основного и кислотного титрования исследовано комплексообразование ионов Mn(II) с пиридоксином в водной среде. Для определения зарядов комплексов применены катионит марки “КУ-2” и анионит марки “АВ-17”. Методом Бьеррума определены значения константы устойчивости образующихся комплексов и приведены их вероятные структурные формулы. Հիմնային և թթվային տիտրման եղանակով ուսումնասիրված է Mn(II)- իոնների կոմպլեքսագոյացումը պիրիդօքսինի հետ ջրային միջավայրում: Կոմպլեքսի իոնների լիցքերի որոշման համար օգտագործվել են «KY-2» տեսակի կատիոնիտ և «AB-17» տեսակի անիոնիտ: The complex-formation of the Mn (ll) ions with pyridoxine in the liquid environment through the methods of basic and acidic titration was studied. For the purpose of determining the charges of the ions in the complex, KY-2 type of cations and AB-17 type of anions have been used. Through Byeroum's method, the stability constants of the developing complexes have been determined and the possible structural formulas are given in the present article.
Keywords: Science; Chemistry; Physical Chemistry